Moderasi beragama di lingkungan desa: peran mahasiswa kkm uin malang dalam membangun harmoni di pandanwangi - Utami, Lukas Sri (Maliki Interdisciplinary Journal, 2025)
The Community Service Program (Kuliah Kerja Mahasiswa/KKM) serves as a platform for students to engage with society while applying academic and social values in real-life settings. Students from UIN Maulana Malik Ibrahim Malang, grouped under Cakrawangsa, conducted their KKM activities in Pandanwangi Village, Diwek District, Jombang Regency. One of their main programs was BINTANG (Together in the Beauty of Tolerance and Joyful Ngabuburit), aimed at promoting religious moderation through engaging and accessible approaches. The activities included watching a short video on tolerance, an interactive quiz, distributing free takjil (light meals for breaking the fast), and holding a communal iftar. The enthusiastic response from children and the local community demonstrated that messages of tolerance can be effectively conveyed through participatory and cultural methods. This program proves that KKM is not only a form of community service but also a medium for fostering awareness of peaceful coexistence within diversity.